One year anaerobic incubation measurements (CH4+CO2) and microbe quantification from samples of Lena Delta collected in 2018 - Mélissa Laurent; Matthias Fuchs; Claire C Treat; Susanne Liebner; Alexandra Runge (PANGAEA, 2023)
The data sets were made during the summer 2021, with samples collected from three cores, at two depths (active and permafrost layers). In total, six samples (3 replicates by samples) were incubated for 67 days at two temperatures (4°C and 20°C). Core sampling were performed during the joint Russian-German LENA 2018 expedition. The data sets were both collected at Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research and GeoForschungsZentrum Helmholtz-Zentrum, Potsdam, Germany. The aim of this study was to understand and quantify how much carbon may be lost during short-term permafrost thaw across different landscape units at the example of study area in the Lena Delta, Siberia. The study measures greenhouse gases (GHG) emissions based on an incubation experiment and focuses on relationships between GHG emissions and microbial abundance shifts during short-term permafrost thaw under anaerobic conditions. The objectives of the study were to: (1) Quantify CH4 and CO2 production during a short-term anaerobic incubation; (2) Establish relationships between CH4 and CO2 production and microbes (methanogens and methanotrophs); (3) and to identify settings and controls that drive gas production rates in thawed permafrost soils.